Do Crude Oil Exports Drive Economic Output in Nigeria? A Trade Data Analysis (1999–2024) - Adesanya, Ayodeji Peter (Global Focus, 2025)
This study analyses how crude oil exports influence economic output in Nigeria using a 26-year dataset from 1999 to 2024. The study addressed three main research questions to include the trends in the value and volume of crude oil exports, the quantifiable relationship between export performance and Gross Domestic Product (GDP), and the extent of economic dependence on crude oil exports. The study adopts a quantitative ex-post facto research design and employs trade data obtained through the United Nations (UN) Comtrade and Nigerian National Petroleum Corporation (NNPC) annual bulletins and GDP Data from the World Bank database for World Development Indicators. The data were analysed with descriptive statistics, Pearson correlation and multiple regression. The findings reveal that the value and the volume of crude oil exports affect GDP, but the export value (measured in USD) correlates very strongly and consistently with economic output compared to the export volume (measured in kilograms). Also, vulnerability of the economy to changes in oil prices was reflected in the close correlation between GDP performance and export revenues. The negative GDP growth rate, particularly during oil price crashes in 2008/2009 and 2014-2016, highlights the macroeconomic weakness of Nigeria. The paper points to the structural dependence on oil, which continues even after a number of diversification policies. It concludes that a sustained economic growth will demand more than just a sound export performance, but a recalibration of the trade structure in Nigeria to become less dependent on crude oil.